The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.14214/sf.1072
|View full text |Cite
|
Sign up to set email alerts
|

In search of hybridity: the case of Karelian spruces

Abstract: Highlights • Karelian spruces have morphology that is typical for P. obovata and characterized with genetic variation, described previously for P. abies. • Karelian spruces evolved due to introgression between P. abies and P. obovata. However, it is unclear whether Karelian spruces could be treated as P. fennica, because unequivocal morphological and genetic characters of the latter are still absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The question of the species specificity of the hap lotypes of the intergenic spacer trnT trnF of cpDNA, which were specified as typical of P. obovata spruces of Siberian origin (Tollefsrud and Spirensen, 2011) and later described by P. Volkova (Volkova et al, 2014) on the material from Karelia remains unclear. The avail able published data, unfortunately, do not conclusively answer the question on how reliably the described haplotypes GCCA and _CCA of the intergenic spacer trnT trnF are associated with the P. obovata species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question of the species specificity of the hap lotypes of the intergenic spacer trnT trnF of cpDNA, which were specified as typical of P. obovata spruces of Siberian origin (Tollefsrud and Spirensen, 2011) and later described by P. Volkova (Volkova et al, 2014) on the material from Karelia remains unclear. The avail able published data, unfortunately, do not conclusively answer the question on how reliably the described haplotypes GCCA and _CCA of the intergenic spacer trnT trnF are associated with the P. obovata species.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, Siberian spruce is characterized by its own set of species spe cific haplotypes of the intergenic spacer trnT trnF. These nucleotide sequences have been published recently (Volkova et al, 2014) and are currently avail able from the database GenBank (GenBank Acc. KF896139 and KF896142).…”
Section: Analysis Of the Polymorphism Of The Intergenic Spacer Trnt Tmentioning
confidence: 99%
“…Yet the phylogeny and history of the two species, as well as the exact limits of their respective ranges and their hybridization zone, remain poorly understood. Morphologically, the two species are distinguished by the length of the cone and the shape of the cone scales; Norway spruce cones tend to be larger, and cone scales are more pointed and sharper than those of Siberian spruce, but in both cases, the change in the traits is more gradual across the range than discrete (Schmidt-Vogt 1974;Popov 2003;Volkova et al 2014). An early study based on ten populations and 26 isozyme loci indicated the presence of a hybrid zone centred around the Urals, but the number of populations was clearly too small to delineate the extend of it (Krutovskii & Bergmann 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Exact limits of the distribution ranges and taxonomic status of P. abies and P. obovata have been much debated since many diagnostic morphological traits of the two species are blurred by introgressive hybridization in their contact zones (cf., Tollefsrud et al, 2015;Tsuda et al, 2016). Intermediate morphological states are described either as clinal or geographic variation without taxonomic recognition (Schmidt-Vogt, 1977;Popov, 1996a;Volkova et al, 2014) or treated at intraspecific taxonomic level (Teplouchoff, 1868;Sukachev, 1928Sukachev, , 1938Lindquist, 1948;Jalas & Suominen, 1973;Schmidt-Vogt, 1974, 1977Hämet-Ahti et al, 1992;Tutin et al, 1993;Jonsell, 2000;Latałowa & Knaap, 2006 etc. ), or as hybrids P. fennica (Regel) Kom.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative taxonomic treatment considers P. abies and P. obovata as infraspecific taxa of a single species (Schmidt-Vogt, 1977;Popov, 1996a;Volkova et al, 2014) based on a lack of morphological and genetic specificity of intermediate forms united under "P. fennica", as well as referring to continuous and adaptive nature of the clinal morphological variation in direction from West to East.…”
Section: Introductionmentioning
confidence: 99%